The efficient neutron-gamma pulse shape discrimination with small active volume scintillation detector - Phan , Van Chuan; Nguyen , Duc Hoa; Nguyen , Xuan Hai; Nguyen , Ngoc Anh; Tuong Thi , Thu Huong; Nguyen , Nhi Dien; Pham , Dinh Khang (Nuclear Science and Technology, 2016)
A small detector with EJ-301 liquid scintillation was manufactured for the study on the neutron-gamma pulse shape discrimination. In this research, four algorithms, including Threshold crossing time (TCT), Pulse gradient analysis (PGA), Charge comparison method (CCM), and Correlation pattern recognition (CPR) were developed and compared in terms of their discrimination effectiveness between neutrons and gamma rays. The figures of merits (FOMs) obtained for 100 ÷ 2000 keVee (keV energy electron equivalent) neutron energy range show the charge comparison method was the most efficient of the four algorithms.